Robot-assisted navigation in atrial fibrillation ablation—Of any benefits? - Petrů, Jan; Škoda, Jan (Cor et Vasa (Brno), 2012)
In recent years, catheter ablation has been established as a safe and effective treatment for atrial fibrillation (AF). The benefits of robotic catheter navigation technology and techniques for AF ablation are currently a frequent topic of discussion. Most clinical trials have suggested that robotic ablation is (at least) as effective as the manual approach. The most important potential advantages of robotic ablation include excellent catheter stability and accuracy of its movement, reduced fluoroscopic time, catheter contact monitoring, improved comfort of the operator during the procedure as they can sit most of the time unexposed to radiation and, last but not least, a very short learning curve potentially allowing for more complicated procedures (persistent forms of AF, structural ventricular tachycardias, congenital heart disease).
Keywords: Atrial Fibrillation; výsledek terapie; Treatment Outcome; katetrizační ablace; dálková navigace; Robotics; Humans; lidé; robotika; Catheter Ablation; fibrilace síní